2020
DOI: 10.30636/jbpa.32.188
|View full text |Cite
|
Sign up to set email alerts
|

Child care policy and child care burden: Policy feedback effects and distributive implications of regulatory decisions

Abstract: The policy feedback literature highlights that the design of public policies can affect recipients’ experience of those policies and programs. In this paper, we examine the largely unexplored distributional implications of market-based early childhood education and care (ECEC) services. We present the results of a quasi-behavioral conjoint survey of 606 parents in the City of Toronto. Grouping parent respondents by income and access to public subsidies, we find evidence that access to public subsidies influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Based on this income data, the percentage of parents reporting that they are eligible for a child care subsidy appears low; however, subsidy eligibility in Ontario is based on a mix of both family income and attachment to the labor force (and/or educational attainment). Moreover, of those we have income data on, nearly 45% of those reporting that they “Don’t Know” their eligibility status have incomes below the median income, which may suggest that informational barriers—rather than income—are impacting subsidy uptake (data not shown; Davidson et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Based on this income data, the percentage of parents reporting that they are eligible for a child care subsidy appears low; however, subsidy eligibility in Ontario is based on a mix of both family income and attachment to the labor force (and/or educational attainment). Moreover, of those we have income data on, nearly 45% of those reporting that they “Don’t Know” their eligibility status have incomes below the median income, which may suggest that informational barriers—rather than income—are impacting subsidy uptake (data not shown; Davidson et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…These few studies, carried out using nonrepresentative samples and including only a few racialized and Indigenous people, showed that the latter were more hesitant about the COVID-19 vaccine. [14][15][16] In addition, studies have considered racialized people as a homogeneous group, often referred to as "visible minorities," and do not provide disaggregated analyses by ethnicity. Moreover, there are only a few studies, mostly qualitative and descriptive, that have conducted disaggregated analysis by race and ethnicity.…”
Section: Introductionmentioning
confidence: 99%